2018
DOI: 10.1124/jpet.118.252650
|View full text |Cite
|
Sign up to set email alerts
|

Nicotine Modulates Growth Factors and MicroRNA to Promote Inflammatory and Fibrotic Processes

Abstract: Idiopathic pulmonary fibrosis (IPF) is a fatal disease that destroys the structure and function of the lungs. Risk factors include advanced age and genetic predisposition. However, tobacco use is the chief modifiable risk factor. The prevalence of tobacco use in IPF reaches up to 80%. Although tobacco smoke contains over 5000 chemicals, nicotine is a major component. Nicotine is a bioactive molecule that acts upon nicotinic acetylcholine receptors expressed on neuronal and non-neuronal cells including endothel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 88 publications
0
15
0
Order By: Relevance
“…A recent study showed an additional role of nicotine‐induced dysregulated growth factors and microRNAs that contribute to the development of pulmonary fibrosis, possibly via altered target genes involved in myogenesis . We found significantly altered sex‐dependent expression of both lipogenic/myogenic and ECM remodeling markers in the lungs of the acute e‐cig exposed mice.…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“…A recent study showed an additional role of nicotine‐induced dysregulated growth factors and microRNAs that contribute to the development of pulmonary fibrosis, possibly via altered target genes involved in myogenesis . We found significantly altered sex‐dependent expression of both lipogenic/myogenic and ECM remodeling markers in the lungs of the acute e‐cig exposed mice.…”
Section: Discussionmentioning
confidence: 49%
“…23,55,56 A recent study showed an additional role of nicotine-induced dysregulated growth factors and microRNAs that contribute to the development of pulmonary fibrosis, possibly via altered target genes involved in myogenesis. 57 We found significantly altered sex-dependent expression of both lipogenic/myogenic and ECM remodeling markers in the lungs of the acute e-cig exposed mice. Based on findings from this acute e-cig exposure model, we speculate that chronic exposure of PG and/or PG with nicotine would also cause lung remodeling as a result of altered lipogenesis/myogenesis, including the activation of ECM signaling.…”
mentioning
confidence: 68%
“…Severe fibrosis evident from increased collagen deposition in nicotine-administered rats, may therefore account for impaired cardiac function observed in this study. Several in vitro studies have shown that nicotine directly increases fibroblast proliferation and collagen deposition via modulation of pro-fibrotic cytokines such as TGFβ, microRNAs, and matrix metalloproteinases (Shan et al, 2009;Khoi et al, 2013;Ebrahimpour et al, 2018). Indeed, TGFβ was widely implicated as a key signaling molecule responsible for nicotine-induced fibrosis in various organs and cells (Rezonzew et al, 2012;Ateyya et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…MiR-199a-3p/5p was reported to suppress EMT in various cancer, such as testicular germ cell tumor, non-small cell lung cancer, head and neck cancer, and so on [ 31 33 ]. But they were also reported to promote the EMT process in hepatic fibrosis and idiopathic pulmonary fibrosis (IPF) [ 15 , 34 , 35 ]. These contradictory results suggest that miR-199a-3p/5p might have different functions in different types of EMT in various diseases.…”
Section: Introductionmentioning
confidence: 99%